A rede de atenção à saúde mental na visão de médicos psiquiatras: A Stultifera Navis contemporânea/ The network of mental health assistance in the vision of psychiatric doctors: The contemporary Stultifera Navis - Malamut, Bernardo Salles; Modena, Celina Maria; Passos, Izabel Christina Friche (Cadernos Brasileiros de Saúde Mental/Brazilian Journal of Mental Health, 2012)
Este artigo versa sobre as incidências do discurso da reforma psiquiátrica na concepção de médicos psiquiatras trabalhadores de um hospital psiquiátrico público brasileiro, utilizando-se da análise do discurso. Focaliza a concepção dos entrevistados sobre o que é a reforma psiquiátrica, sobre os diversos dispositivos da de atenção à saúde mental e seu funcionamento, e sobre a posição do hospital psiquiátrico atualmente. Explicita-se a importância de se analisarem os equipamentos de atenção como dispositivos que produzem discursos específicos. Para tal, vale-se das contribuições de Michel Foucault e de teóricos da reforma psiquiátrica. Verifica-se que a reforma incidiu sobre a prática no hospital como uma forma de controle social. Porém, para os entrevistados, o hospital ocupa um lugar de sustentação dos outros dispositivos da rede substitutiva. Desse modo, os entrevistados compreendem os dispositivos substitutivos funcionando ora em uma lógica diversa da lógica manicomial, ora repetindo o discurso excludente que a reforma visa desmontar. Conclui-se que o paciente psiquiátrico permanece errante pelos serviços de saúde, e que a reforma psiquiátrica ainda necessita avançar no sentido de dar aos sujeitos um outro lugar social. ABSTRACT: This article is about the incidences of psychiatric reform discourse on the ideas of psychiatrists who work in a Brazilian psychiatric public hospital using the discourse analysis. It focus on the interviewees’ concepts about what the psychiatric reform is, the multiple dispositives of the mental health care network and its working method, as well as the current place of the psychiatric hospital in that network. The importance of analyzing health care resources as contrivances that produce particular discourses is stressed. For this objective Michel Foucault’s and others` contributions to the psychiatric reform are considered. The research has shown that the reform affected hospital practices as a form of social control. However, the interviewees consider the hospital an important element in the support of other network contrivances. Thus it is clear that the interviewees conceive the substitute services sometimes working in a different logic than the asylum`s, some other times assuming the same way as of seeing madness. It is concluded that psychiatric patients remain wandering in health care services and that the psychiatric reform still needs to advance in the way of seeing individuals.